(untitled) (Islamic Sciences Journal, 2025)
This research presents a comparative jurisprudential study between Sunni and Imam Shiite perspectives on issues related to marriage and divorce, examining key topics such as guardianship, witnesses, the contractual formula (ṣīgha), irregular (heretical) divorce, and triple divorce pronounced in a single utterance, the requirement of witnesses in divorce, and temporary marriage (mutʿah). The study systematically analyzes points of agreement and disagreement between the two schools, employing an inductive and analytical methodology to evaluate the legal evidence. Primary jurisprudential sources from both traditions are critically examined, with careful attention to textual verification and comparative analysis. The findings indicate that the majority Sunni position upholds the necessity of a guardian, witnesses, and a verbal formula in marriage contracts. Regarding divorce, the study concludes that the most jurisprudentially sound position aligned with the objectives of Islamic law (maqāṣid al-sharīʿah) is that irregular divorces (ṭalāq al-bidʿah) are invalid and that a triple divorce pronounced simultaneously counts as a single revocable divorce. This view is consistent with Prophetic precedent (Sunnah) and the practices of the Rightly-Guided Caliphs. Furthermore, the research argues for the obligatory nature of witnesses in divorce, based on the explicit Quran injunction.